2006
DOI: 10.1210/en.2005-1571
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Multifunctional Protein 2 Is Essential for Lipid Homeostasis in Sertoli Cells and Male Fertility in Mice

Abstract: Inactivation of peroxisomal beta-oxidation in mice, by knocking out multifunctional protein-2 (MFP-2; also called d-bifunctional enzyme), causes male infertility. In the testis, extensive accumulations of neutral lipids were observed in Sertoli cells, beginning in prepubertal mice and evolving in complete testicular atrophy by the age of 4 months. Spermatogenesis was already severely affected at the age of 5 wk, and pre- and postmeiotic germ cells gradually disappeared from the tubuli seminiferi. Based on cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 57 publications
6
53
1
Order By: Relevance
“…These observations suggest that Sertoli cells predominantly use lipids to produce ATP through catabolism of LCFAs. The result is in agreement with a recent report that the lipid droplets in Sertoli cells mainly consist of LCFAs (Huyghe et al 2006). The LCFAs are major energy substrates of cells (Crass 1972, 1977, Saddik & Lopaschuk 1991, Klaus 2004.…”
Section: Discussionsupporting
confidence: 93%
“…These observations suggest that Sertoli cells predominantly use lipids to produce ATP through catabolism of LCFAs. The result is in agreement with a recent report that the lipid droplets in Sertoli cells mainly consist of LCFAs (Huyghe et al 2006). The LCFAs are major energy substrates of cells (Crass 1972, 1977, Saddik & Lopaschuk 1991, Klaus 2004.…”
Section: Discussionsupporting
confidence: 93%
“…Abnormal lipid droplets are observed in hepatocytes and neurons in human patients with DBP deficiency, and it has been suggested that male sterility in a knock-out mouse model correlated with the appearance of large lipid droplets in the testes (38)(39)(40). We propose that common factors in mammalian and C. elegans diets contribute to lipid droplet expansion in mutants with peroxisomal defects.…”
Section: Discussionmentioning
confidence: 76%
“…For calculation, the areas corresponding to the eluted nitrophenylhydrazone derivatives of hexadecanal, octadecanal, and octadecenal were summed up and compared with an external standard (gravimetric solution of hexadecanal dimethyl acetal). Triglycerides, cholesterol, and cholesterylesters were isolated by thin-layer chromatography and analyzed with coupled enzymatic assays as described previously Huyghe et al, 2006a) except for cholesterylesters and triglycerides that were hydrolyzed chemically (5% 5 M KOH in ethanol; 75°C; 90 min). Statistical analysis was done by unpaired Student's t test.…”
Section: Biochemical Analysismentioning
confidence: 99%